Never boring: Non-invasive palaeoproteomics of mummified human skin. (July 2020) - Demarchi, Beatrice; Boano, Rosa; Ceron, Arianna; Bello, Federica Dal; Favero-Longo, Sergio E.; Fiddyment, Sarah; Marochetti, Elisa Fiore; Mangiapane, Gianluigi; Mattonai, Marco; Pennacini, Cecilia; Ribechini, Erika; Woolley, Jos; et al.
Abstract: The scientific analysis of mummified individuals can reveal important details on the way people lived and died in the past. Palaeoproteomic approaches are theoretically suitable for obtaining information on the extent of tissue preservation, on the use of protein-based substances for embalming and/or restoration, as well as for characterising the microbiota from both the individual and the environment. However, these analyses usually require the destruction of a sample of tissue, a practice which is (obviously) discouraged by most museums. Unfortunately, this means that in-depth studies, for example by taking multiple samples from each individual, are seldom feasible. Here we show that a non-invasive sampling technique, based on mixed-bed chromatographic media embedded on ethylene vinyl acetate membranes (EVA), which had previously been used exclusively on historical material, was successful in extracting ancient proteins from the surface of Egyptian mummies. We tested the method on a decontextualised fragment of skin and assessed the endogeneity of its metaproteome by comparison with a procedural blank. Furthermore, we retrieved and authenticated sequences of human collagen and keratin, as well as potential bacterial/fungal biodeteriogens, from the mummy of a young woman (Supp. 16747 of the Museum of Anthropology and Ethnography of the University of Turin) who lived and died during the Old Kingdom of Egypt. Highlights: First application of non-invasive EVA sampling to Ancient Egyptian mummies. Authentic skin proteins recovered from the Old Kingdom mummy of a young woman. Proteomic characterisation of potential fungal/bacterial biodeteriogens.